New humanism: a manifesto - Roy, M. N. (Calcutta, 1961)
The Conference of the Radical Democratic Party of India, held in Bombay during the last week of December 1946, resolved to issue a manifesto incorporating the fundamental principles of New Humanism which it had been developing ever since its foundation six years ago. A Statement of these principles in the form of Theses* was adopted by the Conference. In pursuance of the resolution, a draft of the manifesto to be issued was submitted to the Central Political Council of the party which met on May 23rd to 25th, 1947, to discuss the document. The draft being an elaboration of the theses adopted by the Party Conference, and also of a statement on the international situation issued previously, the Central Political Council of the party approved it on principle.
Keywords: Political Science